PENGEMBANGAN PROTOTYPE DECODING BERDASARKAN TEORI REINFORCEMENT DENGAN PENGUJIAN TAM UNTUK KELANCARAN MEMBACA ANAK - Destyani, Iphonie Amelia (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Kids nowadays have understood Digital Technology, even so by using technology to learn. Some schools in particular TK already using Digital Technology that could be used in the process of teaching and learning. This study developed a prototype to improve decoding fluency reading at TK age of children.  Technology Acceptance Model is used to examine the impact of use acceptance prototype decoding. This study includes two stages, the first stage was the creation of the prototype and the second stage of decoding is testing prototype decoding. In the first stage was the creation of the prototype decoding, participants composed of two TK teachers A and B by doing interviews to obtain data about how to learn to read TK age. In the second study is testing prototype decoding, the participant is 37 students TK A and B by way of word recognition test chill to know knowledge of children before and after using the prototype decoding. As for the questionnaire used for data reception prototype decoding.  The results obtained from research that can improve the decoding capability of prototype students in learning to know letters and read a word on TK aged of children, perceived ease of use and perceived usefulness can affect behavioral intention to use prototype decoding.   Keyword decoding , digital technology,  preschool,  reading technology acceptance model